introduction des bactéries lactiques autochtones à effet probiotique dans l'alimentation de lapin local - BELAID, Chaima; NOUAR, Hind (My University, 2024)
This study aims to evaluate the effects of Lactobacillus plantarum, isolated from wheat-based h’moum, on the productivity and health of local rabbits through a probiotic supplement. Twenty-four rabbits were divided into three groups : a control group (T) and two experimental groups (A and B), receiving 1x10⁶ and 2x10⁶ CFU/ml of probiotic by gavage, respectively, for five weeks. Zootechnical parameters (average daily gain, feed conversion ratio, carcass yield) and effects on biochemical (cholesterol, creatinine, glucose) and hematological parameters (leukocytes and platelets) were studied. Results showed that rabbits receiving higher concentrations of Lactobacillus plantarum exhibited improvements in ADG, particularly in group A (1x10⁶ CFU/ml), as well as better feed efficiency. Regarding meat quality, an increase in carcass yield was observed in group B (2x10⁶ CFU/ml), along with enhanced immune responses, reflected by increases in leukocytes and platelets. Additionally, blood cholesterol levels decreased, suggesting a beneficial effect on cardiovascular health. A sensory test also revealed improved organoleptic quality of the meat, particularly in tenderness and flavor. In conclusion, this study demonstrates that administering Lactobacillus plantarum in the form of a probiotic supplement can improve the productivity, meat quality, and health of local rabbits. This approach, based on indigenous strains, could represent a valuable asset for startup projects, leveraging local resources to enhance the performance of local rabbit farming.
Keywords: Lactobacillus plantarum; local rabbits; probiotic supplement; carcass yield; meat quality